2018
DOI: 10.33451/florafauna.v24i2pp365-370
|View full text |Cite
|
Sign up to set email alerts
|

Municipal Solid Waste Management Evaluating Chemical Characteristics in Bahraich City, (U.P.) India

Abstract: This paper presents an assessment of the existing situation of municipal solid waste management (MSWM) in Bahraich City. The quantity and composition of MSW vary from place to place, and bear a rather consistant correlation with the average standard of living. Field investigations were carried out for quantification, analysis of physico-chemical composition and characterization in disposal site. Studies carried out in these places have revealed that there were many shortcomings in the existing practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The amount of nitrate and phosphate in the present investigation was relatively low. Moderate values of nitrate (0.11-0.42 mg/l) and phosphate (0.026-0.080 mg/l) were recorded, which are similar to the results of Tripathi (2016) and Vatandoost et al (2018).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The amount of nitrate and phosphate in the present investigation was relatively low. Moderate values of nitrate (0.11-0.42 mg/l) and phosphate (0.026-0.080 mg/l) were recorded, which are similar to the results of Tripathi (2016) and Vatandoost et al (2018).…”
Section: Resultssupporting
confidence: 84%
“…CO2, like other gases, readily exchanges with the atmosphere and is supersaturated with respect to the atmosphere. The results of this supportive study are from Tripathi et al (2016), Verma (2017b and c), and Suhaila and CheSalmah (2017), Verma and Prakash (2018). 3: Mean values of water quality parameters of the lake WT-Water temperature, pH, DO-Dissolve oxygen, Free CO2, TA-Total alkalinity, Phosphate (PO4) 3and Nitrate (NO 3-) Total Alkalinity: Carbonates and bicarbonates are the major constituents of lake water, and their concentrations are expressed as total alkalinity The minerals in water from the soil, atmosphere and waste discharge provide the source of alkalinity.…”
Section: Resultsmentioning
confidence: 86%
“…Medusa (6%), Chaetognatha (5%), Carida larva (4%) and Foraminifera was (3%). Diverse investigators such as (Tripathi and Tiwari, 2006;Larik et al, 2007) suggested that for copepod Cyclopsregarded as most common zooplankton species and for cladocerans Moina, Bosmina and Daphnia noted as exceptional. Tripathi and Tiwari (2006) provided evidence concerning to the availability of zooplankton from confined environment and commented that maximum kinds and types of planktonsdocumented in bulk quantity during hot months as compared to less numbers and kinds during cold month alike observation was reported by (Larik et al, 2007) from hatchery.…”
Section: Factors Of Physico-chemicalmentioning
confidence: 99%